Electricity rate regulation and public interest the case of the energy regulatory board and the Manila electric company - Mendoza, Maria Fe Villamejor (2003)
Electricity is considered one of the most basic utilities every household and establishment consume everyday. Like every public utility, any increase in electricity rates, especially with the existing monopoly, of such service will directly affect the public. Regulating the rate of electricity has been a longtime concern of most consumers in the country. This article delves into the ten-year running case of the Energy Regulatory Board (ERB) and the Manila Electric Company (Meralco), with the former granting the latter provisional authority to increase electricity rates, and subsequently reversing that decision four years later. The author discusses the chronological course of events with regard to the case starting from the Energy Crisis in the late 1980s until the 1990s which led to Meralco's petition for rate increase in 1993, followed by its approval by the ERB in 1994, then a reversal of that same decision in 1998 along with the mandatory implementation of a refund program in 2003, as ruled by the Supreme Court to affirm the legality of the refund order. She further provides a number of findings based on the arguments and analyses of all the parties involved in the case, pointing out that while Meralco's refund does good to the consumers, the fact still remains that the series of events that unfolded benefited Meralco more than the public who were made to shoulder the non-operating expenses incurred by the company.
Keywords: Electric Power Industry Reform Act (EPIRA); Electricity industry; Electricity rate regulation -- Case study; Manila Electric Company